The sociological inheritance of the 1960s : historical reflections on a decade of changing thought - Šubrt, Jiří (Emerald Publishing Limited, 2023)
The 1960s saw pioneering changes in the realms of international politics, science, culture and art. Turning this historical lens onto the study of sociology, The Sociological Inheritance of the 1960s reveals both the continuities and the departures the field has seen in its core principles and approaches over the past several decades. Beginning with an overview of society in the '60s, Jirí Subrt provides an important reflection on a period worthy of contemporary reflection. In this context, what new concepts emerged? What were the popular methodological approaches? What controversies and debates emerged? How did sociology form part of a wider landscape of creative explosion throughout the decade? What implications does this have for contemporary sociology? Inspiring an enriched understanding of a legacy still deeply relevant to current issues and concerns across the field, The Sociological Inheritance of the 1960s proves that, despite the half a century that has since passed, we still have much to learn from this rich period of sociological development.
Includes index.
Keywords: Sociology -- History.; Nineteen sixties.; Social Science -- Sociology -- General.; Sociology.; elektronické knihy; electronic books